Conjoint Associations of Gestational Diabetes and Hypertension With Diabetes, Hypertension, and Cardiovascular Disease in Parents: A Retrospective Cohort Study - Pace, Romina; Brazeau, Anne-Sophie; Meltzer, Sara; Rahme, Elham; Dasgupta, Kaberi (American journal of epidemiology, 2017)
The conjoint association of gestational diabetes mellitus (GDM) and gestational hypertension (GH) with cardiometabolic disease has not been well studied. We evaluated a combined GDM/GH risk indicator in both mothers and fathers because of shared spousal behaviors and environments. In the present population-based retrospective cohort study, GH was identified in matched pairs of mothers with GDM or without GDM (matched on age group, health region, and year of delivery) who had singleton live births in Quebec, Canada (1990-2007). A total of 64,232 couples were categorized based on GDM/GH status (neither, either, or both). Associations with diabetes, hypertension, and a composite of cardiovascular disease (CVD) and mortality were evaluated using Cox proportional hazard models (from 12 weeks postpartum to March 2012). Compared with having neither GDM nor GH, having either was associated with incident diabetes (hazard ratio (HR) = 14.7, 95% confidence interval (CI): 12.9, 16.6), hypertension (HR = 1.9, 95% CI: 1.8, 2.0), and CVD/mortality (HR = 1.4, 95% CI: 1.2, 1.7). We found associations of greater magnitude among participants who had both (for diabetes, HR = 36.9, 95% CI: 26.0, 52.3; for hypertension, HR = 5.7, 95% CI: 4.9, 6.7; and for CVD/mortality, HR = 2.4, 95% CI: 1.6, 3.5). Associations with diabetes were also observed in fathers (for either, HR = 1.2, 95% CI: 1.1, 1.3; for both, HR = 1.8, 95% CI: 1.4, 2.3). In conclusion, we found associations of a combined GDM/GH indicator with cardiometabolic disease in mothers and with diabetes in fathers, with stronger associations when both GDM and GH were present.